Recreational runner’s pace and numerical pain rating scale - Batari, Andi Dinda (Indonesian Journal of Sport Management, 2024)
A number of runner problems, such as injuries and muscular soreness, can cause pain after running. Overindulgence in running volume and pace increases may be significant factors in the development of injuries. Numerical pain rating scale (NPRS) used to measure pain severity. The purpose of this study is to find correlations between pace and pain scale with NPRS. The study was an observational analytic with cross-sectional approach, sample included 39 recreational runners aged over 18 who reside in Indonesia. The results of this showed respondents were on average 33.2 years old (SD = 9.9) and included 66.7% male, with an average running frequency of 9.2 times per month (SD = 7.84), average pace is 6.98 (SD = 1.54), the NPRS varies from 0 to 6. Location of pain after running were toes (10.3%), sole of feet (15.4%), heel (10.3%), calves (43.6%) and had no complaints of pain (20.5%). The correlation between pace and pain scale with NPRS was significant (p<0.05), and was a positive correlation. There was a correlation between pace and NPRS; the slower of pace, the higher the pain. The implications for recreational runners were that they may decrease post-run pain by increasing their pace gradually by regular do-run exercising.